Facing the music : a critical enquiry into 'the dodo-bird verdict' to develop music psychotherapy theory - Beek, RoseAnna van (2015)
‘The dodo-bird verdict’ represents a boggling outcome of research that shows no significant difference between the outcomes of a variety of psychotherapy treatments. Not being able to scientifically discriminate between psychotherapeutic treatments, casts doubt on their theoretical underpinnings, and even on their efficacy. This in turn presents professionals who use psychotherapeutic techniques - including music therapists - with a conundrum: What can explain this inability? And what can be done to solve the problem? Conceptual research methods were used to analyse literature in order to answer these questions. Various weaknesses were identified, both in theory construction and in research methodology within the field, which could possibly have led to the occurrence of the dodo-bird verdict. It seems that much of the conundrum could be solved by transitioning to a new theoretical framework and by incorporating new research paradigms; reimagining psychotherapy as a contextual treatment, and researching it based on systems thinking and chaos theory. Though much research remains to be done, in this new light psychotherapy - and with it music psychotherapy - stands as an effective and relevant treatment.